Contribución al análisis de la ironía en Viernes de dolores : un acercamiento a la perspectiva pragmática. - Yánez Leal, Adelso Luis. (University of Ottawa (Canada), 1996)
This thesis is a pragmatic analysis of the irony in the novel Viernes de dolores by Miguel Angel Asturias. It presents the following hypothesis: the irony in this novel breaks away from the monological discourse characteristic of the narrative of social realism in Latin America. In order to carry out this analysis a corpus of ironic enunciatory sentences was selected which correspond to three levels of irony: the irony between the narrator and the narrated context, in the dialogue between characters and the author's relation with the reader. The theoretical framework of the methodology used includes a summary of past and present-day linguistic pragmatic studies in which some of the most well-known researchers in this field are cited. It is divided into three parts: the evolution of linguistics which dealt with only the message conveyed to one which deals with the speakers and the communication situation, a historic summary of pragmatic linguistics and the analysis of irony from a pragmatic point of view.
Keywords: Literature, Latin American.